ERROR CORRECTION, FEEDBACK, AND ACTION RESEARCH IN AMERICAN LITERATURE CLASSROOM: WHY NOT? - Didik Murwantono (Universitas Islam Sultan Agung, 2016)
Error correction and feedback are two indispensable factors in shaping literature technique and theory. In this case, these techniques were applied to students who took American Multicultural Literature at College of Languages, UNISSULA Semarang. The students were asked to make any literary criticism toward several literary works from different cultural backgrounds. Both teacher and students have significant roles in those preferences. If teacher and students both understand the purpose of certain correction techniques and agree their use, feedback is more likely to be productive. This article also covers action research by using two cycles. It finds that students can improve their capabilities and skills in writing of an intellectual diary. It can be seen from the result of observation both test-1 and test-2 which had the progress in index from 0.45 to 0.52. Hence collaborative writing and reader-response criticism has given great contribution toward students’ motivation in learning American literature.